Reducing emissions from deforestation and forest degradation (REDD) in Indonesia: options and challenges for fair and efficient payment distribution mechanisms - Noordwijk, Meine van; Purnomo, H.; Peskett, L.; Setiono, B. (World Agroforestry Centre, 2008)
The objective of REDD payment distribution mechanisms is to support policies and measures that reduce deforestation and degradation through transfer of revenues from international REDD funds or carbon markets to (or within) national levels. This may provide benefits of three types: a) shared responsibility for reducing a major driver of global climate change, b) financial payments and co-investment that exceed the economic opportunities foregone from decisions to maintain carbon stocks, and c) co-benefits through the other environmental service functions that well-maintained forests can provide. Given its track record of high emissions from land use and land use change of an estimated 2.5 Gt CO2e year-1, Indonesia provides a huge opportunity as well as serious challenge to reduce emissions. We report here on a series of stakeholder consultations and focus group discussions to identify options and challenges. To ensure demonstrable results on emission reduction, REDD mechanisms must be effective in targeting the wide range of agents involved in deforestation and degradation, learning lessons from past and ongoing conservation efforts that have apparently failed. They must reward good performance and incentivize improved performance compared to reference scenarios, and adequately compensate agents that suffer losses from changed practices. International payments are likely to be performance based, both in terms of emission reduction at national scale and the environmental and social impacts of the system, meaning that accountability, transparency, risk management, adequate benefits transfer and administration mechanisms will be essential for attracting investment. Indonesia will be effectively competing for attention and REDD funds with other countries with currently high pemissions and/or large forest areas. A strong international ‘bargaining position’ requires that internal conflicts and strategic positioning be overcome